The future is battery electric: Climate change mitigation in road freight transport - Wolf-Peter Schill; Julius Jöhrens; Dominik Räder; Hendrik Beeh; Josef Klingl; Markus Werner (DIW Weekly Report, 2024)
Road freight transport must switch to alternative drive technologies, such as battery-electric or hydrogen vehicles, to mitigate its impact on the climate. Preliminary results from an ongoing research project show that the fleet of battery-electric trucks as well as the number of models on offer have recently grown significantly, albeit from a very low level. This is not the case for hydrogen trucks. Considerable amounts of investment from the private sector are flowing into the charging infrastructure. Compared to hydrogen trucks, battery-electric vehicles have major advantages when it comes to energy efficiency, foreseeable energy costs, and their expected and realistic contribution to climate change mitigation. Policymakers should therefore set a clear focus on ramping up battery-electric trucks while expanding the charging infrastructure, the fast charging network more vigorously in particular. To face possible challenges, especially when it comes to grid connections, battery swapping systems, or overhead line systems- which have a large technological overlap with battery-electric trucks-could be tested further. Furthermore, the energy efficiency advantages of battery-electric trucks should be considered in the greenhouse gas reduction quota system.
Keywords: L62; Q42; R40; R48; 330; road freight transport; battery-electric vehicles; electric road systems; hydrogen